2021
DOI: 10.1088/1757-899x/1011/1/012039
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal of Cashew (Anacardium occidentale Linn) leaves, nutshells, and peduncle bagasse ashes extracts against sooty mould fungi (Capnodium sp)

Abstract: Different concentrations of cashew (Anacardium occidentale Linn) leaves, nutshells, and peduncle bagasse ashes extract evaluated for growth inhibition of Capnodium sp and the antifungal activity. Results revealed that different concentration of cashew leaves, nutshells, and peduncle bagasse ashes extracts showed values difference of absorbance (DA) ranging from 0.00 to 0.42. All the concentrations of extracts showed significant inhibition in the spore germination of sooty mould. The highest levels caused maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The bioactive compound of CNSL can prevent the inhibition of mycelial growth and spore production. Similarly, in a study conducted by Andayanie et al (2021), CNS extract had a high level of total polyphenolic, flavonoid content, pH, and a low value of titratable acidity be attributed to its potent antifungal activity. The same trend has been observed in bioactive polyphenol compounds, singly or in combination.…”
Section: Discussionmentioning
confidence: 85%
“…The bioactive compound of CNSL can prevent the inhibition of mycelial growth and spore production. Similarly, in a study conducted by Andayanie et al (2021), CNS extract had a high level of total polyphenolic, flavonoid content, pH, and a low value of titratable acidity be attributed to its potent antifungal activity. The same trend has been observed in bioactive polyphenol compounds, singly or in combination.…”
Section: Discussionmentioning
confidence: 85%
“…The soybean plantation can adapt to Grumusols, Inceptisol, Ultisols, Alfisol soil types. However, productivity decreased due to the use of the intercropping system [3]. Another study showed that soybean planting could adapt well on dryland with a dry climate and implement under the teaks to meet the domestic demand for soybeans.…”
Section: Introductionmentioning
confidence: 99%